Pap Smear Diagnostic Test Towards Gold Standard Histopathology In Cervic Cancer: Uji Diagnostik Pap Smear Terhadap Gold Standard Histopatologi Pada Kanker Serviks - Anik Handayati; Putri, Tiara Dewanti; Sri Sulami Endah Astuti (Medicra (Journal of Medical Laboratory Science/Technology), 2024)
Cervical cancer is the second most common cancer in the world. Screening examination plays an important role in early detection of cervical cancer so that it can reduce mortality. Pap smear is an initial examination to detect the presence of abnormal cells in the cervix. This study aims to determine the sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of pap smear examination by comparing them to histopathological examination as the gold standard. The design of this study was an observational study with secondary data obtained from the medical records of cervical cancer patients who had performed pap smears as well as histopathological examinations at the Anatomical Pathology Laboratory Installation, RSPAL dr. Ramelan Surabaya for the period January 2020 to March 2022. The data will be sorted based on inclusion and exclusion criteria. Data that pass the inclusion criteria will be tested using crosstabulation and then proceed to the diagnostic test. The sensitivity value is 97%, specificity value is 88%, accuracy value is 96%, positive predictive value is 98%, and negative predictive value is 79%. Pap smears have a fairly good diagnostic value for diagnosing cervical cancer.